Sustainable Development Of Organic Farming In Bulgaria - State And Opportunities - Roumen Otouzbirov; Todorka Atanasova; Iskra Nencheva (The Central European Review of Economics and Management (CEREM), 2019)
In recent years, Bulgarian organic agriculture is one of the sectors that is developing rapidly despite of the overall stagnation in Bulgarian agriculture and is continuously growing in farming areas as well as in number of farmers. This development is related to the suitable conditions for its adoption in our country - ecologically preserved areas; awareness and willingness of consumers to eat healthy; the realization of the benefits to the environment and rural areas; institutional support for organic farming and the good perception of organic products on international markets.Aim: Examine the condition and opportunities for development of sustainable organic farming in Bulgaria.Design / Research methods: The methods used to complete the tasks are systematic and comparative analysis, an estimated constructive method; method of statistical groupings, inductive and deductive methods of forming generalizations.Conclusions / findings: Organic farming combines the best environmental practices, biodiversity heightening, nature conservation and high production standards. At the same time, it provides public goods in terms of rural development and responds to specific consumer demand for clean and healthy products.Originality / value of the article: Organic production is an international, European and national priority. Organic farming plays an important part in the Common agricultural policy of EU for the 2014-2020 period, as well as for Bulgarian agricultural policy as a tool in regards to the sustainable management of natural resources, the preservation of food quality and safety and the humane farming means.
Keywords: Q13; Q18; Q57; 330; agriculture; organic farming; agricultural policy